Analysis Of Abortion Laws In India: The Necessity Of A Global March To Guarantee Reproductive Freedom (Journal of Namibian Studies : History Politics Culture, 2023)
The author discusses how the current sub-classification of pregnancies in Indian abortion laws, which is a selective privilege, conflicts with the autonomy of individuals over their own bodies. The MTP Act of 1971 was enacted at a time when most countries lacked comparable legislation. As a result of the preference for male foetuses over female foetuses in India, female foeticide and pre-natal determination of sex were criminal offences at the time, making it a significant breakthrough. Regarding abortion, the paper examines the extent and rationale for State intervention as parens patriae to protect the health and wellbeing of both the mother and the embryo at the national and international level. The global situation appears to be dire. According to a UN Report, 98% of countries permit abortion to save a woman's life. This is a very encouraging statistic. In actuality, a woman's existence in the twenty-first century is limited to her limbs and body. This is supported by the fact that only 34% of countries permit abortion solely on the request of the woman in cases of unintended pregnancy. In the context of eugenic model versus woman's autonomy, the recent issue of Poland, where a predominantly archaic Catholic mindset was conceptualised in actuality and where the most recent court ruling held that abortions for foetal abnormalities violate its Constitution, has been discussed. The paper examines European jurisprudence on abortion laws and the effect of COVID-19 on women's access to healthcare in India's rural and urban areas. The suggestions have been summed up in the current Indian laws and the need for all nations to move towards upholding womanhood and the autonomy of her privacy, rights, and decisions.